Inhibitory effect of natural compounds on quorum sensing system in Pseudomonas aeruginosa: a helpful promise for managing biofilm community - Shariati, Aref; Noei, Milad; Askarinia, Marzieh; Khoshbayan, Amin; Farahani, Abbas; Chegini, Zahra (Frontiers in Pharmacology, 2024)
Pseudomonas aeruginosa biofilm is a community of bacteria that adhere to live or non-living surfaces and are encapsulated by an extracellular polymeric substance. Unlike individual planktonic cells, biofilms possess a notable inherent resistance to sanitizers and antibiotics. Overcoming this resistance is a substantial barrier in the medical and food industries. Hence, while antibiotics are ineffective in eradicating P. aeruginosa biofilm, scientists have explored alternate strategies, including the utilization of natural compounds as a novel treatment option. To this end, curcumin, carvacrol, thymol, eugenol, cinnamaldehyde, coumarin, catechin, terpinene-4-ol, linalool, pinene, linoleic acid, saponin, and geraniol are the major natural compounds extensively utilized for the management of the P. aeruginosa biofilm community. Noteworthy, the exact interaction of natural compounds and the biofilm of this bacterium is not elucidated yet; however, the interference with the quorum sensing system and the inhibition of autoinducer production in P. aeruginosa are the main possible mechanisms. Noteworthy, the use of different drug platforms can overcome some drawbacks of natural compounds, such as insolubility in water, limited oral bioavailability, fast metabolism, and degradation. Additionally, drug platforms can deliver different antibiofilm agents simultaneously, which enhances the antibiofilm potential of natural compounds. This article explores many facets of utilizing natural compounds to inhibit and eradicate P. aeruginosa biofilms. It also examines the techniques and protocols employed to enhance the effectiveness of these compounds.